Investigation of Structural, Magnetic, and Optical Properties of ZnO Codoped with Co and Cd - Lubna Mustafa; Safia Anjum; Salma Waseem; Rehana Zia; Rameesha Choudhry; Shahid M. Ramay; Asif Mahmood; Shahid Atiq; Salah Ud-Din Khan (Advances in Condensed Matter Physics)
Co and Cd have been codoped in ZnO using a simple solid state reaction technique to synthesize dilute magnetic oxide semiconductors of composition Zn0.9Co0.1−xCdxO (x = 0.0-0.1 with an increment of 0.02). Hexagonal wurtzite structure has been obtained for samples up to x = 0.06, using X-ray diffractometry. However, at x = 0.08 and 0.1, secondary peak of CdO is observed. Raman spectra of the samples have been obtained in 200–800 cm−1 range. UV-VIS spectrophotometer is used to study the optical properties, which shows that band gap energy decreases with the increase in Cd concentration. A weak ferromagnetic behavior was evident which decreased further by adding Cd in the series. Room temperature resistivity measurements performed using four-point probe technique showed that their values lie in the semiconductor range. Structural morphology of the samples has been investigated by a scanning electron microscope and grain size has been determined. Raman spectra and Fourier transform infrared spectroscopy revealed the successful incorporation of Co and Cd ions into the host ZnO lattice.